Business intelligence solution and decision making in the administrative management of the drugstores - Maldonado Ruiz, Italo (2014)
The overall objective is to support decision making in the management of sales through the drugstores archangel development of a business intelligence solution. For this, we propose a "basic - applied" research, because this research sought to develop a solution based on existing knowledge, which will be complemented by the experience of the researchers, after which it will be applied to a case study and one quasi - experimental research, because they are going to compare the results obtained before the solution is applied to the results obtained when applying the solution. In the present research, the study population were the meetings held for the decision making process in the pharmacy sales which organized a total of 52 meetings per year. To determine the sample to be carried out during the research work, the formula for finite populations sampling was used determining a population size of 52 meetings a year with one meeting per week and with a confidence level of 97.5% with a success rate of 50% and an accuracy of 8%. According to the formula, a sample size of 39 meetings was obtained. The methods and procedures for data collection are based on interviews and observation. The documentary analysis will be formalized to find the whole process regarding the decision making process of business management in the sales area. Interviews were then conducted to determine the current situation or problems of the company and finally surveys were applied to the personnel involved in the process of decision making in order to meet all the uncertainties and document all the mandatory requirements. Therefore, in the present research about, we seek to be defined as strategic points the establishment of sales strategies, marketing and analysis of the "Business Plan", but based on historical data of the company.